Harnessing inherently hierarchical microstructures of plant biomass to construct three-dimensional nanoporous nitrogen-doped carbons as efficient and durable oxygen reduction electrocatalysts. Issue 69 (6th December 2019) - Tang, Hongqu; Wei, Shilin; Yang, Chuangchuang; Bai, Peiyao; Qi, Jiawei; Zhang, Wendu; Yu, Lejian; Xu, Lang
Abstract : Naturally hierarchical microstructures of E. tirucalli are utilized to prepare a nanoporous nitrogen-doped carbon-based metal-free ORR electrocatalyst that is superior to the benchmark Pt/C catalyst in catalytic activity and durability. Abstract : Exploiting the natural structures of plants to prepare high-performance carbon-based electrocatalysts is highly desirable. Herein, the inherently hierarchical microstructures of Euphorbia tirucalli ( E. tirucalli ) are employed to construct three-dimensional nanoporous nitrogen-doped carbons that act as efficient and durable electrocatalysts towards the oxygen reduction reaction (ORR). During the preparation process, agar is used in order to reduce the dissipation of nitrogen and to protect the fine structures of E. tirucalli . The as-prepared ORR catalyst, with a high density of pyridinic and graphitic nitrogens, presents a high catalytic activity (onset potential of 0.97 V vs. RHE, half-wave potential of 0.82 V vs. RHE, limiting current density of 5.64 mA cm −2 and Tafel slope of 59 mV dec −1 ), four-electron pathway, low peroxide yield, long-term stability (current retention of 95.3% after 50 000 s) and strong methanol tolerance in 0.1 M KOH, all superior to the benchmark 20% Pt/C commercial catalyst. This work demonstrates an effective method for the utilization of inherently hierarchical microstructures of plant biomass to make efficient and durable carbon-based metal-free ORR electrocatalysts.